2015
DOI: 10.1007/s10916-015-0236-0
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Hemodynamic Responses Associated With Force and Speed Imagery for a Brain-Computer Interface

Abstract: Functional near-infrared spectroscopy (fNIRS) is an emerging optical technique, which can assess brain activities associated with tasks. In this study, six participants were asked to perform three imageries of hand clenching associated with force and speed, respectively. Joint mutual information (JMI) criterion was used to extract the optimal features of hemodynamic responses. And extreme learning machine (ELM) was employed to be the classifier. ELM solved the major bottleneck of feedforward neural networks in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…The LDA-based classification (achieving a 3.6% increase in the accuracy for MI tasks using the hybrid modality) showed that the NIRS signals contributed to the detection of the active/idle state as well as to the detection of active classes to confirm early activity detection. In two other similar studies, the MI of both the force and speed of hand clenching was decoded using hybrid EEG–NIRS (Yin et al, 2015b,c). In the first case, the extreme learning machine classifier was used to decode the responses associated with the force and speed imagery of the hand with an accuracy of 76.7%, whereas, for the second case (Yin et al, 2015c), the features of EEG and NIRS were combined and optimized using the joint mutual information selection criterion, again utilizing the extreme learning machines, in which case, the resulting average classification accuracy for the force and speed of hand clenching was 89%.…”
Section: Hardware Combinationmentioning
confidence: 99%
“…The LDA-based classification (achieving a 3.6% increase in the accuracy for MI tasks using the hybrid modality) showed that the NIRS signals contributed to the detection of the active/idle state as well as to the detection of active classes to confirm early activity detection. In two other similar studies, the MI of both the force and speed of hand clenching was decoded using hybrid EEG–NIRS (Yin et al, 2015b,c). In the first case, the extreme learning machine classifier was used to decode the responses associated with the force and speed imagery of the hand with an accuracy of 76.7%, whereas, for the second case (Yin et al, 2015c), the features of EEG and NIRS were combined and optimized using the joint mutual information selection criterion, again utilizing the extreme learning machines, in which case, the resulting average classification accuracy for the force and speed of hand clenching was 89%.…”
Section: Hardware Combinationmentioning
confidence: 99%
“…The signal mean, signal peak, and signal slope in the 2–7 s (i.e., 5 s) windows from the onset were found to yield better classification accuracies for fNIRS-BCI using HRs ( Hong et al, 2015 ; Naseer and Hong, 2015 ). Like fMRI, the frequently used classifiers for the fNIRS features discrimination include LDA, SVM, extreme machine learning, Bayes classifiers, and neural networks ( Chan et al, 2012 ; Yin et al, 2015 ; Bui et al, 2016 ; Kim et al, 2016 ; Naseer et al, 2016b ; Ding et al, 2017 ).…”
Section: Role Of the Initial Dip In Bcimentioning
confidence: 99%
“…Shin and Jeong used fNIRS to detect left and right leg movement tasks in a four-class BCI [ 42 ], and in prior studies we presented preliminary offline classification results using left and right foot tasks separately in a four-class motor-imagery-based fNIRS-BCI [ 22 , 23 ]. fNIRS has also been used to examine differences in motor imagery due to force of hand clenching or speed of tapping [ 34 ].…”
Section: Introductionmentioning
confidence: 99%